Circulating Cell-Free Mitochondrial DNA in Cerebrospinal Fluid as a Biomarker for Mitochondrial Diseases. (3rd August 2021) - Trifunov, Selena; Paredes-Fuentes, Abraham J; Badosa, Carmen; Codina, Anna; Montoya, Julio; Ruiz-Pesini, Eduardo; Jou, Cristina; Garrabou, Glòria; Grau-Junyent, Josep M; Yubero, Dèlia; Montero, Raquel; Muchart, Jordi; et al.
Abstract: Background: Mitochondrial diseases (MD) are genetic metabolic disorders that impair normal mitochondrial structure or function. The aim of this study was to investigate the status of circulating cell-free mitochondrial DNA (ccfmtDNA) in cerebrospinal fluid (CSF), together with other biomarkers (growth differentiation factor-15 [GDF-15], alanine, and lactate), in a cohort of 25 patients with a molecular diagnosis of MD. Methods: Measurement of ccfmtDNA was performed by using droplet digital PCR. Results: The mean copy number of ccfmtDNA was approximately 6 times higher in the MD cohort compared to the control group; patients with mitochondrial deletion and depletion syndromes (MDD) had the higher levels. We also detected the presence of both wild-type mtDNA and mtDNA deletions in CSF samples of patients with single deletions. Patients with MDD with single deletions had significantly higher concentrations of GDF-15 in CSF than controls, whereas patients with point mutations in mitochondrial DNA presented no statistically significant differences. Additionally, we found a significant positive correlation between ccfmtDNA levels and GDF-15 concentrations ( r  =   0.59, P  =   0.016). Conclusion: CSF ccfmtDNA levels are significantly higher in patients with MD in comparison to controls and, thus, they can be used as a novel biomarker for MD research. Our results could also be valuable to support the clinical outcome assessment of MD patients.